2012
DOI: 10.1186/1471-2229-12-35
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profile analysis of E3 ligase and hormone-related genes expressed during wheat grain development

Abstract: BackgroundWheat grains are an important source of food, stock feed and raw materials for industry, but current production levels cannot meet world needs. Elucidation of the molecular mechanisms underlying wheat grain development will contribute valuable information to improving wheat cultivation. One of the most important mechanisms implicated in plant developmental processes is the ubiquitin-proteasome system (UPS). Among the different roles of the UPS, it is clear that it is essential to hormone signaling. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 68 publications
(115 reference statements)
1
23
0
Order By: Relevance
“…As of date, some crucial and important signaling pathways in the developing grain have never been explored in wheat (Capron et al 2012). Much work remains to be done before the precise roles of signals in grain development and the roles of signal transduction pathways that coordinate the response to the environment are understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As of date, some crucial and important signaling pathways in the developing grain have never been explored in wheat (Capron et al 2012). Much work remains to be done before the precise roles of signals in grain development and the roles of signal transduction pathways that coordinate the response to the environment are understood.…”
Section: Discussionmentioning
confidence: 99%
“…The differential expression of genes involved in the UPS and plant hormone pathways suggests that phytohormones and UPS crosstalk might play a critical role in the wheat grain developmental process. Some E3 ligase and hormone-related genes seem to be up-or downregulated during the early and late stages of the grain development (Capron et al 2012).…”
Section: Signaling Related Proteinsmentioning
confidence: 99%
“…Transcription factor UniGenes were retrieved from the wDBTF database (34). E3 ligase and hormone-responsive UniGenes were recovered from the NCBI and TAIR databases using all A. thaliana and O. sativa E3 ligase and hormone-responsive sequences as the query in homology searches using the BLASTn, BLASTx and tBLASTx programs (36). The BLAST hits were filtered using an e-value threshold of 10 − 5 and an alignment length exceeding 80 bp.…”
Section: Data Content Database Architecture and Web Interfacementioning
confidence: 99%
“…A total of 39 029 transcripts from the UniGene set (build #55) and 1613 transcription factors from the wDBTF database not present in the UniGene set are spotted on the custom T. aestivum NimbleGen 40 k microarray (36). Previous studies have shown that 18 140 (44.6%) of these transcripts are expressed during T. aestivum grain development (47).…”
Section: Identification and Annotation Of Unigenes Specifically Exprementioning
confidence: 99%
See 1 more Smart Citation